Evaluation of the taste-active and volatile compounds in stewed meat from the Chinese yellow-feather chicken breed. (10th January 2018) - Qi, Jun; Wang, Hu-hu; Zhou, Guang-hong; Xu, Xing-lian; Li, Xiao; Bai, Yun; Yu, Xiao-bo
ABSTRACT: Effects of stewing time (1, 2, and 3 h) on the levels of taste-active and volatile compounds were measured. The flavor characteristics of the stewed yellow-feather chicken meat were assessed with sensory evaluation and electronic nose. Results showed that increasing stewing time significantly decreased the contents of taste components such as free amino acids, 5′-nucleotides, minerals. Inosine 5′-monophosphate and chloride were the major umami-related compounds in stewed meat and decreased significantly during stewing. The taste-active values of the equivalent umami concentration decreased from 283.2 to 38.7 after 3 h of stewing. In contrast, increasing stewing time improved aroma levels. The volatile compounds mainly included pentanal, hexanal, heptanal, octanal, ( E )-2-octenal, nonanal, ( Z )-4-decenal, decanal, ( E, E )-2, 4-decadienal, 1-pentanol, and 1-octen-3-ol. With increased stewing time, aldehydes significantly decreased ( P  < 0.05), whereas alcohols significantly increased ( P  < 0.05). The high-intensity aroma after 2 h of stewing could be attributed to 1-pentanol and 1-octen-3-ol. The aroma scores of the chicken meat were at maximum after stewing for 3 h. The overall flavor characteristics tended to stabilize after 2 h of stewing. In general, stewing improved the aroma but decreased the taste components in the chicken meat, especially within the first 2 h. The data herein not only provides insight into the changes in odor and taste of chicken meat during cooking, but also guidelines for improving the stewing process.